Distribution and composition of suspended solids in the snow cover of the western sector of the Russian Arctic - E. I. Kotova; D. P. Starodymova; A. S. Lokhov; O. P. Netsvetaeva (Лëд и снег, 2025)
The results of a study of the content and composition of suspended solid matter in snow samples taken in the western mainland of the Russian Arctic (Kola Peninsula, North of Arkhangelsk Oblast, Nenets Autonomous Okrug) are presented. The concentrations of insoluble forms of 40 elements were determined by ICP-MS method in samples collected at the end of the 2022/23 winter season. The sampled snow had pH values ranging from 5.0 to 9.2. Lower pH values were found in melted snow of the Kola Peninsula. High pH values are typical for snow from the territory of the Nenets Autonomous Okrug. The average content of insoluble matter in snow over the whole investigated area was equal to 3.4 mg/l. The increase in the content of suspended matter occurs locally due to anthropogenic factors and natural features. The insoluble matter in snow near Monchegorsk is enriched with Ni, Bi, Cu, Co, Co, V, Pb, As, Sb and Mo. The production of the apatite-nepheline ores accounts for an increase of manganese, aluminum, titanium and SPM in the samples near the town of Apatity. A significant source of pollution of the snow cover with insoluble forms of vanadium and nickel found on the western coast of the Kola Bay is the coal transshipment activities in the port of Murmansk. In the north of the Arkhangelsk region, the shipbuilding and ship repair enterprises in the city of Severodvinsk serve as a source of antimony and copper in the insoluble substance of snow. Increasing content of manganese, titanium, nickel, vanadium, and cobalt has been determined in the suspension in the area of the Northern Dvina River mouth that is caused by influence of the thermal power plant of the Arkhangelsk agglomeration. In background areas, the suspended matter is enriched with lead and arsenic. The data obtained will make possible to estimate the load on Arctic ecosystems, which are vulnerable even under a small anthropogenic impact, and provide information for understanding the processes occurring in nature and further rational management of Arctic ecosystems.